Wind Energy Meteorology Atmospheric Physics for Wind Power Generation - Emeis, Stefan (Green Energy and Technology,, 2018)
This book offers an introduction to the meteorological boundary conditions for power generation from wind - both onshore and offshore, and provides meteorological information for the planning and running of this important renewable energy source. It includes the derivation of wind laws and wind-profile descriptions, especially those above the logarithmic surface layer, and discusses winds over complex terrains and nocturnal low-level jets. This updated and expanded second edition features new chapters devoted to the efficiency of large wind parks and their wakes and to offshore wind energy.